The E-Print Industry and Bookseller Market: A Strategic Perspective - Nodoushani, Omid; Yang, Chalie (Competition Forum, 2011)
Keywords: dept.mgt; peer-reviewed

Industrial Democracy in The Knowledge Society - Nodoushani, Omid; Robbins, Gregory Gadiel (Competition Forum, 2019)
Keywords: dept.mgt; peer-reviewed

A Creative Use of Films to Enhance Emotional Awareness and Cultural Intelligence - Yang, Chulguen Charlie; Nodoushani, Omid (Research Yearbook, 2012)
Keywords: dept.mgt; peer-reviewed

Leadership: A gateway to organizational innovation - Nodoushani, Omid; Stewart, Carol; Wall, Alison (Competition Forum, 2017)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Cultivating Employees Using Maslow's Hierarchy of Needs - Stewart, Carol; Nodoushani, Omid; Stumpf, Jason (Competition Forum, 2018)
Stress caused by climates of fear in the workplace is sapping employee decision-making and causing conflict in the workplace. While hard to quantify, it is easy to understand why intelligent and engaged employees are the ideal: there are fewer mistakes and higher productivity. The primary metric used to frame the reasons for motivation is Maslow's Hierarchy of Needs. It is also vitally important to understand the power balance between employees and employers. By the very nature of employment, employers have less need for a particular employee unlike the employee who cannot afford to be unemployed.
Num Pages: 67-75 Place: Indiana, United States
Keywords: Business And Economics; Compensation; Competition; Corporate culture; Emotions; Employees; Employers; Employment; Employment security; Empowerment; Games; Handbooks; Happiness; Job satisfaction; Personal computers; Physiology; Software; Stress; Success; Work environment; Workers; dept.mgt; peer-reviewed

Organizations' investment in education - Nodoushani, Omid; Stewart, Carol; Escobar, Jessica (Competition Forum, 2016)
Keywords: dept.mgt; peer-reviewed

Genetically engineered food and genetically modified organisms - Nodoushani, Omid; Sintay, Jayme; Stewart, Carol (Competition Forum, 2015)
Keywords: dept.mgt; peer-reviewed

Recycling and Its Effects on the Environment - Nodoushani, Omid; Stewart, Carol; Kaur, Manpreet (Competition Forum, 2016)
Consumers and businesses have an ethical obligation to do their part to reuse or recycle unwanted items. However, while some consumers and businesses do reuse or recycle e-waste, glass, metal, plastic, paper or textiles, more could be done. Even with environmentalists warning of potential chemical hazards these items produce in landfills, an estimated 85 percent of landfills are filled with unwanted waste. The recycling industry along with local government run media campaigns to raise awareness; however, as a result consumers and businesses may be experiencing information overload which may have a negative impact on consumers ' recycling efforts.
Num Pages: 5 Place: Indiana, United States
Keywords: Communication; Consumers; Consumption; Electronic waste; Electronics; Energy consumption; Environmental impact; Environmental protection; Environmentalists; Greenhouse gases; Information overload; Landfill; Natural resources; Plastics; Raw materials; Recycling; Textiles; dept.mgt

Workplace bullying: A growing epidemic - Wall, Alison E.; Smith, Robert A.; Nodoushani, Omid (Competition Forum, 2017)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Bullying in the workplace: The great balancing act of victim rights and organizational policies - Wall, Alison E.; Smith, Robert A.; Nodoushani, Omid (Journal of Competitiveness Studies, 2018)
Bullying in the workplace is considered a growing epidemic and organizations are struggling to ensure appropriate responses and protocol as there is currently no individual statutory remedy. This paper provides a synthesis of current research regarding workplace bullying, legal policies, efforts to promote remedial legislation and organizational responsibility and outcomes. Workplace bullying is addressed from several perspectives including organizational consequences, characteristics of both victims and perpetrators, the current state of legislation and best practices for organizational policy. The paper also provides a discussion of developing issues related to increased technology and social media usage.
Keywords: BULLYING in the workplace; CYBERBULLYING; VICTIMS of bullying; VIOLENCE in the workplace; WORK environment; dept.mgt; peer-reviewed; ⛔ No DOI found

The Green Energy Sector - Nodoushani, Omid; Van den Abbeele, Isaline; Stewart, Carol (Competition Forum, 2015)
Thinking "Green" has become a significant economic trend lately. This research paper offers a better understanding of the background facts of the current hype surrounding "Green Energy." First, the problem of global warming is investigated. Europe has taken a lead role in the fight against global warming in order to meet their objective of 20% renewable energy production by 2020. Many possibilities exist to transform raw biomass into bioenergy fuels, which can then be used for specific energy production purposes: electricity production, warming or transport. Biodiesel, bioethanol, biogas and many other fuels can be produced from biomass.
Num Pages: 6 Place: Indiana, United States
Keywords: Alternative energy; Alternative energy sources; Biomass; Carbon dioxide; Chlorofluorocarbons; Climate change; Energy industry; Environmental impact; Global warming; Greenhouse effect; Greenhouse gases; Nobel prizes; Renewable resources; Studies; Temperature; Trends; dept.mgt